Exploring TikTok Live Shopping : How Uses and Gratifications Theory, Network Size, and Digital Celebrities Drive Continuous Purchase Intentions - Hidayati, Eva Laela; Maria Apsari Sugiat; Maya Aryanti (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the influence of Uses and Gratifications Theory (U&G Theory) dimensions—including hedonic gratification (perceived enjoyment), utilitarian gratification (perceived utility and self-presentation), and social gratification (social presence) as well as perceived network size on continuous purchase intention. In addition, the study explores the mediating role of perceptions of digital celebrities in the context of live streaming shopping for modest fashion products on TikTok. A quantitative approach was employed using a survey method involving 429 TikTok users who had purchased modest fashion items through live streaming. The data were analyzed using covariance-based Structural Equation Modeling (SEM) with AMOS software. The findings reveal that perceived utility, self-presentation, and social presence positively influence continuous purchase intention, whereas perceived enjoyment shows no significant effect. Furthermore, perceived network size has a significant impact on perceived enjoyment, perceived utility, and social presence. The study also demonstrates that perceptions of digital celebrities mediate the relationship between perceived network size and all dimensions of U&G Theory. These results enrich the literature on consumer motivation and behavior in live streaming commerce and offer strategic implications for businesses in designing relevant content and collaborations to foster customer loyalty.